ChemInform Abstract: Coibacins A and B: Total Synthesis and Stereochemical Revision. Issue 26 (1st July 2014) - Carneiro, Vania M. T.; Avila, Carolina M.; Balunas, Marcy J.; Gerwick, William H.; Pilli, Ronaldo A.
Abstract Coibacin A (I) is prepared in 12 steps and 3.4% overall yield.